2022
DOI: 10.1155/2022/8741158
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Numerical and Analytical Assessment of the Shear Strength of RC and SFRC Beams Externally Strengthened with CFRP Sheets

Abstract: This study investigates numerically utilizing nonlinear finite element (ANSYS software) and analytically the shear response of the Reinforced Concrete (RC) beams. Different beams are considered in the current study, such as RC, steel fibre reinforced concrete (SFRC) without web reinforcement, and RC externally reinforced in the shear zone with carbon fibre reinforced polymer (CFRP) sheets. Nonlinear finite element model (FEM) is designed to simulate the performance of the designed beams. The results of FEM are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(29 reference statements)
0
4
0
2
Order By: Relevance
“…Utilization of quantitative FE simulations improves comprehension of the behavior and more affordable parametric studies. Previous research [31][32][33][34][35][36][37][38][39] concluded that the fracture analysis of the slabs and beams could be correctly predicted using the finite element programs.…”
Section: Applications Of Finite Element In the Analysis Of Frp Rc-mem...mentioning
confidence: 99%
See 1 more Smart Citation
“…Utilization of quantitative FE simulations improves comprehension of the behavior and more affordable parametric studies. Previous research [31][32][33][34][35][36][37][38][39] concluded that the fracture analysis of the slabs and beams could be correctly predicted using the finite element programs.…”
Section: Applications Of Finite Element In the Analysis Of Frp Rc-mem...mentioning
confidence: 99%
“…Barour and Zergua [46], and Barour et al [37] utilized the FE modeling to explore the shear region behavior of RC-beams externally strengthened using FRP strips. The NLFE ANSYS program produced findings that were in alignment with prior literature experimental data.…”
Section: Applications Of Finite Element In the Analysis Of Frp Rc-mem...mentioning
confidence: 99%
“…Several authors have been employed with the numerical package ANSYS to validate their experimentally tested results and further did parametric studies with the verified numerical models (Barour et al, 2022;Hawileh et al, 2011;Hawileh, 2012;Jawdhari et al, 2018;Banjara and Ramanjaneyulu, 2019;Kadhim et al, 2019;Choobbar et al, 2019;Hawileh et al, 2019aHawileh et al, , b, 2010Hawileh et al, , 2013Abuodah et al, 2021;Nawaz et al, 2016;Abu-obeidah et al, 2015;Naser et al, 2021). The one-way RC slab with openings was modeled in the ANSYS domain, and the developed models were validated by the past experimental study performed by the authors (Kaya and Anil, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have been employed with the numerical package ANSYS to validate their experimentally tested results and further did parametric studies with the verified numerical models (Barour et al ., 2022; Hawileh et al ., 2011; Hawileh, 2012; Jawdhari et al ., 2018; Banjara and Ramanjaneyulu, 2019; Kadhim et al ., 2019; Choobbar et al ., 2019; Hawileh et al. , 2019a, b, 2010, 2013; Abuodah et al ., 2021; Nawaz et al ., 2016; Abu-obeidah et al ., 2015; Naser et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Схожій проблемі присвячені статті [8][9][10] зарубіжних вчених. Цикл робіт [11][12][13] присвячений моделюванню балок, зміцнених листами з полімеру, армованого вуглецевим волокном. Не менш цікаві роботи в ANSYS наших співвітчизників [14 -15].…”
unclassified